Fluticasone furoate/vilanterol once daily improves night-time awakenings in asthma patients with night symptoms: Post hoc analyses of three randomized controlled trials. (3rd August 2018) - Kerwin, Edward; Barnes, Neil; Gibbs, Michael; Leather, David; Forth, Richard; Jacques, Loretta; Yates, Louisa J.
ABSTRACT: Objective : Symptoms, including night-time awakenings, affect the quality of life of people with asthma. Fluticasone furoate/vilanterol (FF/VI) reduces exacerbations, improves lung function, and rescue-free and symptom-free 24-hour periods in patients with asthma. These post hoc analyses compared daytime and night-time symptoms in patients with asthma who received FF/VI, versus FF, fluticasone propionate (FP) or placebo. Methods : Daytime and night-time symptoms were collected via electronic daily diary cards in three Phase III randomized studies of once-daily FF/VI in patients with uncontrolled asthma on inhaled corticosteroids (ICSs) ± long-acting beta2 agonists ( n = 609/1039/586). Endpoints included change from baseline in symptom-free days and nights (analyzed by Analysis of Covariance, covariates: baseline, region, sex, age, and treatment), time for patients to achieve seven consecutive symptom-free nights (analyzed by Cox proportional hazards' model, covariates as above), and proportion of patients experiencing 100% symptom-free nights per week (analyzed by logistic regression, covariates: percentage of symptom-free nights, sex, age, and treatment). Results : Improvements in symptom-free days and nights were generally observed for all treatments. More patients who received FF/VI experienced 100% symptom-free nights in the last week of the treatment period than patients who received ICS alone or placebo. FF/VI also reduced time to achieve seven consecutive symptom-free nights. Patients with at least one night of symptoms at baseline experienced an additional 2.7 and 2.0 symptom-free nights per week with FF/VI 100/25 µg, versus 1.9 and 1.7 with FF alone; similar findings were seen with FF/VI 200/25 µg. Conclusions : Benefits in terms of symptom-free days and nights were observed for patients receiving FF/VI versus comparators in these post hoc analyses.